Stability analysis of roundness profiles of drawn tubes - Augustin, Gorog; Ingrid, Gorogova (Manufacturing Technology Journal, 2020)
The geometric accuracy is significant property of the product. For semi-finished products, this accuracy may also affect the accuracy of the final product (the resulting mechanical component). Geometric accuracy (inaccuracy) can be transmitted from one operation to the next in production - technological heredity arises. It is, therefore, essential to analyze the deviations on the produced areas and take measures to ensure that the negative effect of one operation was not transferred to the next operation. It is insufficient to analyze only the numerical values of the measured deviations. It is necessary to directly analyze the measured profiles in the field of macro geometry. The paper presents a stability analysis of roundness profiles measured on the drawn tube. The analysis uses knowledge from harmonic analysis and from the Fourier series. The measured roundness profiles are divided into individual harmonic components. Arithmetic means of amplitudes of individual harmonic components are moni-tored. There were analyzed parameters determining the stability of the profile - standard deviations.
Keywords: drawn tubes; technological heredity; roundness profiles; harmonic analysis; Fourier series